Penerapan Docker Kontainer dan Kriptografi Pengamanan Data Pesan Teks Dengan Metode Diffie Hellman - Febrianto M Ipu; Arita Witanti (LPPM Universitas Mercu Buana Yogyakarta, 2021)
Data security is very important at this time because a lot of data contains important and limited information for other people to know. Cryptography is one of the right steps in securing information data and isolating all data in one container. This research tries to implement an algorithm that has been developed previously and unites the required data into one container with container technology. The first step in conducting this research is to identify the problem and will continue with learning about cryptography and container technology. The main idea of this research is to build a very secure system by isolating every data or container that will be used in development. The results of this study show that the cryptographic system uses the Diffie Hellman algorithm to secure every text message and container used to unify data with Docker Container technology. From this research it can be concluded that the system is able to secure data with the Diffie Hellman algorithm and the data isolated into one Docker container can work well with the system.